PENGEMBANGAN MEDIA PEMBELAJARAN VIPOT BERBASIS PENDEKATAN SAINTIFIK PADA MATERI DAUR AIR - Fathonah, Aida; Andriana, Encep; Yandari, Indhira Asih Vivi (STKIP Persada Khatulistiwa Sintang, 2024)
This research aims to develop learning media in the form of vipots on water cycle material at elementary school. The subjects of this research were class V students at Pasirmaggu State Elementary School. The method used in this research is Research and Development with the ADDIE model with stages of analysis, design, development, implementation, evaluation. Data collection was carried out through observation, interviews and questionnaires. The results of the research show that Vipot learning media is suitable in using as a learning media. It can be seen from the assessment results by media and material expert validators. Validation by media experts obtained a score of 89.95% with very feasible criteria, while validation by material experts obtained a score of 86.65% with very feasible criteria. While, the results of the questionnaire showed a student response of 80.76% with very good criteria. Thus, it can be concluded that this vipot learning media is effective to improve the students’ understanding at class V in SDN Pasirmaggu on the water cycle material.